Environmental and Biological Impact of Fly Ash and Metakaolin-Based Alkali-Activated Foams Obtained at 70°C and Fired at 1,000°C - Leonelli, Cristina; Turk, Janez; Poggetto, Giovanni Dal; Catauro, Michelina; Traven, Katja; Mauko Pranjić, Alenka; Ducman, Vilma (Frontiers in Chemistry, 2022)
Alkali-activated foams (AAFs) are inorganic porous materials which can be obtained at temperatures well below 100 °C with the use of inorganic wastes as aluminosilicate precursors. In this case, fly ash deriving from Slovenian power plant has been investigated. Despite the environmental benefits per se, due to saving of energy and virgin materials, when using waste materials, it is of extreme importance also the evaluation of potential leaching of heavy metal cations from the alkali-activated foams. This article serves to investigate whether or not 1000 °C fired alkali-activated fly-ash and metakaolin-based foams, cured at 70 °C are environmentally friendlier options compared to unfired ones and attempts to explain the rationale of the results. The eventually firing process at 1000 °C apart from improving technical performance could reinforce heavy metals cations entrappment within the aluminosilicate matrix. Since technical performance was also modified by addition of different types of activators (K-based or Na-based), as well as by partial replacement of fly-ash with metakaolin, LCA analysis was performed to quantify the effect of these additions and processes (curing at 70 and firing at 1000 °C) in terms of global warming potential. The leaching test indicated that none of the alkali-activated material is classified as hazardous, not even the as-received fly-ash as component of new AAF. The highest impact on bacterial colonies was found in samples which did not undergo firing procedures, i.e. which were cured at 70 °C, that induced the reduction of bacterial E. faecalis viability. The second family of bacteria tested, E. coli, appeared more resistant to the alkaline environment (pH = 10–12) generated by the unfired AAMs. Cell viability recorded the lowest value for unfired alkali-activated materials produced from fly-ash and K-based activators. By LCA it has been shown that: i) changing Na-based activators to K-based activators increases environmental impact for up to 23% ; ii) replacing of part of fly-ash with metakaolin results in relatively higher environmental footprint (the exception is impact on abiotic depletion of elements with an increase for 9%); and finally iii) firing at 1000 °C contributes significantly to the environmental footprint of AA foams.